ANALISIS KINERJA PETUGAS SURVEILANS KESEHATAN DALAM UPAYA PENGENDALIAN TUBERKULOSIS DI KOTA SEMARANG - Anggrayunita Rahma; Antono Suryoputro; Chriswardani Suryawati (Medika Respati : Jurnal Ilmiah Kesehatan, 2020)
Performance Analysis of Health Surveillance Officer in Controlling Tuberculosis in Semarang City Background: The biggest challenge for the implementation of National Health Insurance is participation in the informal sector. Various backgrounds in the informal sector are reluctant to join BPJS Health membership because because they have never got dissemination of information on BPJS, have irregular monthly income, and object to monthly premium. Objective: Determining factors influencing demand for Health BPJS Kesehatan among merchants in Klaten Market, Klaten District, Central Java. Methods: The study was conducted in Klaten Market on 3-8 September 2019. The research design was cross sectional with a sample of 170 respondents. The sampling technique is accidental sampling. The analysis used was the Kendall Tau test (⍺ = 0.05). Results: Based on the Kendall Tau test results obtained income factors (p-value 0,000), premium amount (p-value 0,000), age (p-value 0.643), education (p-value 0.042) and information exposure (p-value 0.010). Conclusion: There is an influence of income, premium amount, education and information exposure on BPJS Health demand and there is no effect of age on BPJS Health demand.